Pesquisa em psicologia do esporte e o cenário de periódicos científicos específicos - Fábio Hech Dominski (Universidade Estadual do Oeste do Paraná, 2019)
Sport psychology research and the specific journals scenario. Background: There is a remarkable growth in the production of knowledge in the field of sports psychology (SP). The knowledge produced by researchers occurs through the publication of their work in the format of articles in scientific journals. There are no analyses in the literature considering the specific journals of the area and their characteristics. Objective: To discuss about the current scenario of specific journals related to SP. Methods: This is a documentary research about the SP journals. The following data were extracted and analyzed: country, institution, publisher, publication language, metrics (JCR - ISI Web of Science, SJR, Citescore and SNIP - Scopus, and index h5 - Google Scholar), periodicity, publication period, and number of articles published in 2018. Results: It was observed 14 journals related to SP. Most of them are from United States, three from Spain and three from United Kingdom. Brazil, Italy and Netherlands showed one journal each. Most of the journals publish in English language (13 of 14). The impact factor ranged from 0.64 to 6.90, and five journals do not show this metric in 2018. In this year, the journals published from 11 to 144 articles. Conclusion: From the analysis of the specific scientific journals of the SP, it was found that the journals with highest quality are from the United States and Europe. In Brazil, there is a need to strengthen the existing specific journal in the area, which can be done by unifying the organizations that work in professional practice and scientific research of SP.